APPLIED PHOTOGRAPHY FOR TKP COFEE HOUSE’S COMPANY PROFILE - Asyfahani, Cahya Naufal (Arty: Jurnal Seni Rupa, 2020)
The purpose of this study project is to produce a company profile design that will be combined with product photography according to company needs, so as to convince potential franchisees to use the TKP Coffee House services and can confirm the positioning of the TKP Coffee House as a cafe that has superior product quality. The design of the company profile combined with this photography will be published in printed form, namely booklets, and in the online form, namely social media, and websites. The process of designing a company profile with a combination of photography through several stages of the process of creating a sequence of pre-production processes, production processes, and post-production processes. The design of a company profile with a combination of photography is expected to help the TKP Coffee House build its image in the audience and potential franchisees, provide added value, and making the TKP Coffee House cafe able to compete with its competitors.